Selling for dummies - Hopkins, Tom, author; Kench, Ben, author (Chichester, England : John Wiley & Sons, 2007)
"Have you ever persuaded your family to take a vacation to a spot where you really wanted to go? Or have you ever convinced your boss to give you a promotion or raise? Have you ever sold your friends on trying a great new restaurant or negotiated with a teacher and received a higher grade? If so, you've been involved in "the art of selling."" "Every day, you're faced with situations where it's essential to communicate effectively, to gain cooperation from others, and to be a good listener. Selling For Dummies, by world-renowned sales trainer Tom Hopkins, will teach you the essential "selling skills" you need to be successful. You'll get the tools, techniques, and strategies you need to quickly master the steps to selling success -- all in a fun and easy-to-understand format! Book jacket."--BOOK JACKET
Pt 1. The Art of Selling --Pt. Ch. 1 You Don't Need a Uniform or a Fancy Suit -- Ch.2. The Seven Step Selling Cycle -- Ch.3 Enjoying Selling as a Hobby -- Pt.2 Preparation is the Key -- Ch.4 Knowing Your Market -- Ch.5 Knowing What You Sell -- Ch.6. Using Technology to Your Advantage -- Pt.3 The Anatomy of a Sale -- Ch. 7. Finding the People Who Want What You Sell -- Ch.8 Making Appointments the Easy Way --Ch.9 Finding the Best Way to Proceed with Client -- Ch.10 The Pitch: Presenting Yourself and Your Offering Properly -- Ch.11 Addressing Customer Concerns -- Ch.12 Easing the Ssale to Close -- Ch.13 Referrals ; The Best Way to Grow your Business
Includes index.
In English text.
Keywords: Marketing; Selling